Uma Ferramenta para Ensino e Aprendizado de Exploração de Espaço de Projeto de Arquiteturas de Processadores na Era de Dark-Silicon - Erick Rocha Amorim (2023)
Design space exploration is an activity useful in many engineering contexts, and considered crucial for the design of MPSoCs (often deployed in mobile devices and embedded systems). Therefore, it is a relevant topic for the future microeletronic technicians of the Brazilian industry. MultiExplorer is a tool initially proposed to support research in the field of processor architectures’ design space exploration (DSE) in the dark-silicon era. Many studies were published in international conferences and scientific journals, using MultiExplorer in a range of applications, from mitigating the dark silicon on multicoreand many-core architectures and performing heterogeneous computing DSE, to DSE on systems based on general-purpose computing on graphics processing units and cloud computing resource allocation. However, despite the recommendation to include DSE in the curriculum of engineering and computer science programs by the ACM (Association for Computing Machinery), and it’s relevance for the industrial development of the country, references to this topic in the curricula of those programs in Brazil are scarce. This work proposes the use of an enhanced version of the MultiExplorer DSE tool as an educational resource for teaching and learning dark silicon aware design space exploration on multicore architectures. This work features the enhancement of the tool for better usability, and a case study using the tool on a extracurricular minicourse for undergraduate Computer Science and Computer Engineering programs in Brazil. This has resulted in a more mature software architecture for the tool, transition to a open source code, and the establishment of a graphical user interface as to allow better student interaction with the tool. The prospect from the case study was positive.